TANGGUNG JAWAB DIREKSI ATAS KELALAIAN DALAM PENGURUSAN PERSEROAN TERBATAS (STUDI KASUS PUTUSAN NOMOR: 439/PDT.G/2011/PN.JKT.SEL) - AHMAD YASIR ARAFAT (PREMISE LAW JURNAL, 2017)
Recently, managing a corporation has become a public spotlight since it is not professional, inefficient, and not transparent so that it is difficult to maintain its existence. Public assessment on the performance of board of directors raises a question about the root of the problem which has caused the performance of board of directors to be inefficient and not optimal in managing a corporation. The formula of the problems were as follows: how about the position of board of directors in a corporation according to law on corporation in Indonesia, how about the responsibility of board of director for their negligence in managing a corporation which harms the company, and how about panel of judges’ role in applying the provisions in Law No. 40/2007 on Corporation, related to board of directors’ responsibility for their negligence which caused harm for the company in the Ruling No. 439/Pdt.G/2011/PN.JKT.SEL.The research used judicial normative and descriptive analytical method. The materials of the research were primary, secondary, and tertiary legal materials. The data were gathered by conducting library study and understanding the Ruling No. 430/Pdt.G/2011/PN.JKT.SEL. The data were analyzed systematically by using qualitative method and the conclusion was drawn deductively.Keywords: Responsibility, Director, Negligence, Corporation Management